The gas-surface interaction of a human-occupied spacecraft with a near-Earth object. Issue 9 (1st November 2016) - Farrell, W.M.; Hurley, D.M.; Poston, M.J.; Zimmerman, M.I.; Orlando, T.M.; Hibbitts, C.A.; Killen, R.M.
Abstract: NASA's asteroid redirect mission (ARM) will feature an encounter of the human-occupied Orion spacecraft with a portion of a near-Earth asteroid (NEA) previously placed in orbit about the Moon by a capture spacecraft. Applying a shuttle analog, we suggest that the Orion spacecraft should have a dominant local water exosphere, and that molecules from this exosphere can adsorb onto the NEA. The amount of adsorbed water is a function of the defect content of the NEA surface, with retention of shuttle-like water levels on the asteroid at 10 15 H2 O's/m 2 for space weathered regolith at T ∼ 300 K.